Efektifitas Model Pembelajaran Problem Based Learning Berbantuan Mit App Inventor terhadap Kemampuan Pemahaman Konsep Matematika - prasetiyani, aneira; supandi, supandi; rahmawati, noviana (Universitas PGRI Semarang, 2026)
The purpose of this study was to determine the effectiveness of the Problem Based Learning learning model assisted by MIT App Inventor on the ability to understand mathematical concepts compared to conventional learning. This type of research is quantitative research. The population of this study was class VIII students of SMP Negeri 26 Semarang in the 2024/2025 academic year. The sample of this study was class VIII D and VIII F using the cluster random sampling technique. The data collection techniques used were test methods, documentation and interviews. The data analysis techniques used were t-test, n-gain test and classical completeness test. The results of this study obtained: (1) Students' understanding of mathematical concepts using the Problem Based Learning learning model assisted by MIT App Inventor is better than conventional learning models, (2) The application of the Problem Based Learning learning model assisted by MIT App Inventor is effective in improving students' mathematical understanding abilities. (3) Students' understanding of mathematical concepts using the Problem Based Learning learning model assisted by MIT App Inventor achieved classical completeness.